Natural Variation in Photosynthetic Traits Measured at Pre and Post Anthesis Stages for 36 Field Grown Wheat Genotypes - Maity, Sourav; Srinivasan, Vishnupriya; Dutta, Puspendu; Roy, Suvedu Kumar; Das, Saikat (International Journal of Bio-resource and Stress Management, 2024)
The experiment was conducted during November–March of 2018–19 and 2019–20 at the University Farm of Uttar Banga Krishi Viswavidyalaya, Pundibari, Cooch Behar, West Bengal, India to assess the variability of 36 selected wheat genotypes for key morpho-phenetic traits as well as photosynthetic parameters and also to study their associations pattern at various growth stages. Photosynthetic parameters were recorded by Gas exchange (GE) measurement under open field condition at both pre- and post-anthesis stages The genotypes showed significant variation for photosynthetic parameters such as Pn, E, Ci, and gs, for pre-anthesis measurements while in post-anthesis measurements, all the parameters found to be non-significant except Pn. All these traits showed higher value in pre-anthesis stage indicating higher physiological efficiency at this stage. Most of the traits showed high heritability coupled with higher genetic advance except gs in both pre and post anthesis stages indicating higher role of additive gene action. This study found no significant correlation between pre and post-anthesis photosynthetic traits and grain yield or biomass when all cultivars were compared. Cultivars with the highest photosynthetic performance did not equate with the highest yields. However, path analysis revealed a positive and high direct effect of E, WUE (both pre and post anthesis stage); gs, (Pre-anthesis stage only) on grain yield while a negative direct impact of BY and Pn (pre-anthesis stage). PCA analysis also confirmed the importance of photosynthetic parameters such as Pn, E, gs, Ci, LUE, and WUE measured at both pre and post-anthesis stages towards the divergence of wheat genotypes.